Dynamic changes in the gut microbiota of SPF Bama piglets during breast and formula feeding - Zhang, Chengcheng; Liu, Zhengjiang; Yu, Huan; Shen, Yuanyuan; Lu, Lu; Kong, Fanli; Sun, Wei; Wei, Xiaoyuan; Jin, Long; Ge, Liangpeng; Zeng, Bo (Frontiers in Microbiology, 2025)
The gut microbiota plays a crucial role in the growth performance, health status, and welfare of pigs. Breast milk is a key factor in the colonization of gut microbiota and the overall health of newborn piglets. With advancements in breeding technology, formula milk has been widely adopted as a substitute for breast milk. This study aims to investigate the effects of sow feeding (natural breastfeeding) and formula milk feeding on the gut microbiota of specific pathogen-free (SPF) Bama pigs. Using metagenomic sequencing technology, we analyzed 114 fecal samples to uncover the impacts of different feeding methods on gut microbial diversity, dominant microbial populations, metabolic functions, carbohydrate-active enzymes (CAZymes), and antibiotic resistance genes (ARGs). The results revealed significant differences in the structure and function of gut microbiota between the breast milk (BM) group and the formula milk (FM) group at day 21. The BM group exhibited higher gut microbial diversity compared to the FM group, along with more extensive metabolic functions at both the gene and species levels. Notably, the FM group demonstrated higher activity in galactose metabolism and glycan metabolism, particularly at day 21. Additionally, the FM group showed significantly higher levels of ARGs against glycopeptide antibiotics at days 21 and 28 compared to the BM group. This study also found that breastfeeding and formula feeding differentially regulate the metabolic activity of gut microbiota and the expression of related enzymes, which may have long-term effects on nutrient absorption and disease resistance in pigs. These findings provide new insights into how different feeding methods shape the gut microbiota of pigs and offer a scientific basis for optimizing feeding strategies and improving breeding efficiency.